RURAL TOURISM DEVELOPMENT: HOW TO ATTRACT THE RESIDENTS’ PARTICIPATION? A STUDY OF THE CENTRAL HIGHLANDS, VIETNAM - Thi Phuong Thao Hoang; Thi Ha Trinh (Tạp chí Khoa học Đại học Đà Lạt)
The main aim of this study is to measure the impact of factors including sense of place, perceived benefits, perceived costs, and quality of life on the residents’ willingness to assist in rural tourism development in the Central Highlands, Vietnam. SPSS software was used to check the suitability of the model, and partial least squares structural equation modeling (PLS-SEM) was used to run a regression analysis of the balance equations and to measure the level of impact between factors. The regression equation then provided the interaction between the variables as the explanation for the hypotheses. The statistical results of 443 survey responses were analyzed from five provinces of this region. Quality of life showed a positive impact on residents’ willingness to support rural tourism development, while perceived benefits related to cultural and social issues had negative impacts. These findings and the discussion may aid policymakers in planning strategies for rural tourism development in the Central Highlands, Vietnam.